2019
DOI: 10.1016/j.molcel.2019.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Glutarylation of Histone H4 Lysine 91 Regulates Chromatin Dynamics

Abstract: Highlights d H4K91glu is a new histone mark enriched at promoters of highly expressed genes d H4K91glu destabilizes nucleosome by affecting (H2A/H2B) and (H3/H4) 2 interaction d H4K91glu is regulated by KAT2A and Sirt7 as its ''writer'' and ''eraser,'' respectively d H4K91glu regulates chromatin structure and dynamics in response to DNA damage

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
166
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(172 citation statements)
references
References 56 publications
4
166
0
2
Order By: Relevance
“…Our data reveal a substantial overlap between the identified CML sites and other PTM, particularly acetylation and ubiquitination, suggesting that CML modification may interfere with biological processes mediated by these PTM. For instance, K92 on histone H4, which became substantially more modified with CML during aging, has been reported to be also a target of acetylation and glutarylation, which are both involved in the regulation of chromatin structure and dynamics in response to DNA damage (Bao et al, 2019;Ye et al, 2005). Furthermore, global glycation of histone 3 has been shown to compete with acetylation and methylation thereby disrupting chromatin architecture (Zheng et al, 2019;Zheng et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Our data reveal a substantial overlap between the identified CML sites and other PTM, particularly acetylation and ubiquitination, suggesting that CML modification may interfere with biological processes mediated by these PTM. For instance, K92 on histone H4, which became substantially more modified with CML during aging, has been reported to be also a target of acetylation and glutarylation, which are both involved in the regulation of chromatin structure and dynamics in response to DNA damage (Bao et al, 2019;Ye et al, 2005). Furthermore, global glycation of histone 3 has been shown to compete with acetylation and methylation thereby disrupting chromatin architecture (Zheng et al, 2019;Zheng et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11] The activity of SIRT7 is still not as well understood, with reports suggesting various deacylase activities. [12][13][14][15] Numerous studies have suggested that modulating sirtuin activities has therapeutic potential for treating various cancers, metabolic disorders, and neurodegenerative diseases. 5,11,[16][17] Additionally, such compounds can be used as tools to further study the enzymes in the family and their individual roles in the cell.…”
Section: Benzyl ((S)-mentioning
confidence: 99%
“…酶活性, 但具体机制尚待研究 [31,32] . 最新研究又发现, SIRT7通过去组蛋白H4K91的戊二酰化调控染色质凝 聚 [33] . 由此可见, SIRT7具有多种酶活性(表2), 现有文 献报道与SIRT7相互作用的蛋白质很多, 却不发生去 乙酰化, 如mTOR, Myc和TFIIIC2等 [34] , 很有可能是通 过其他酶活性调控的.…”
Section: 生型unclassified
“…但是其E3泛素连接酶至今没有确定. 最近, Yan等人 [41] 发现, SIRT7在精氨酸甲基转移酶PRMT6的 表 2 SIRT7催化底物及相关生物学功能 [7] p53 去乙酰化 抵抗细胞凋亡 [11] PAF53 去乙酰化 前体核糖RNA的合成和成熟 [12] U3-55k 去乙酰化 前体核糖RNA的合成和成熟 [13] GABPβ1 去乙酰化 线粒体功能 [14] NPM1 去乙酰化 衰老 [15] PGK1 去乙酰化 糖酵解 [16] FKBP51 去乙酰化 乳腺癌细胞中的AKT失活和化疗敏感性增加 [20] CDK9 去乙酰化 转录延伸 [17] FOXO3 去乙酰化 阻止LPS刺激时发生的细胞凋亡 [21] DDB1 去乙酰化 调节DDB1-CUL4的相互作用和CRL4活性 [18,19] SMAD4 去乙酰化 抑制乳腺癌肺转移 [22] DDX21 去乙酰化 基因组稳定性 [23] FBL 去乙酰化 rRNA合成 [25] H3K36 去乙酰化 rDNA异染色质沉默和基因组稳定性、转录延伸或DNA的损伤修复 [10] H3K37 去乙酰化 未知 [10] RanK37 去乙酰化 抑制p65向核外转移 [27] ATM 去乙酰化 DNA损伤修复 [26] WDR77 去乙酰化 抑制癌细胞生长 [24] OSX 去丙酰化 促进骨形成 [30] H3K36/K37 去丁酰化 未知 [10] H3K122 去琥珀酰化 DNA修复过程中的染色质重塑 [29] H4K91 去戊二酰化 调控染色质凝聚 [33] 催化下发生388位精氨酸甲基化, 抑制SIRT7的H3K18 去乙酰化酶活性, 从而调控葡萄糖传感和线粒体生物 发生. 此外, SIRT7的酶活性还受到染色质组成性DNA…”
Section: Sirt7的调控unclassified